2015
DOI: 10.1002/pmh.1305
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary field trial of a putative research algorithm for diagnosing ICD-11 personality disorders in psychiatric patients: 2. Proposed trait domains

Abstract: This field trial examines the discriminant validity of five trait domains of the originally proposed research algorithm for diagnosing International Classification of Diseases (ICD)-11 personality disorders. This trial was carried out in South Korea where a total of 124 patients with personality disorder participated in the study. Participants were assessed using originally proposed monothetic trait domains of asocial-schizoid, antisocial-dissocial, anxious-dependent, emotionally unstable and anankastic-obsess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 30 publications
0
32
0
2
Order By: Relevance
“…As noted in the introduction, a systematic review reported similar higher order dimensions in other patient samples (Mulder et al, ). A study attempting to validate our prior proposed domains suggested that while the Anankastic, Detached and Dissocial domains showed good discrimination, the emotionally unstable and anxious dependent ones did not (Kim et al, ). The Detached, Anankastic and Negative Affective domains are consistent with most higher‐order factor studies.…”
Section: Discussionmentioning
confidence: 99%
“…As noted in the introduction, a systematic review reported similar higher order dimensions in other patient samples (Mulder et al, ). A study attempting to validate our prior proposed domains suggested that while the Anankastic, Detached and Dissocial domains showed good discrimination, the emotionally unstable and anxious dependent ones did not (Kim et al, ). The Detached, Anankastic and Negative Affective domains are consistent with most higher‐order factor studies.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, there is a vast body of empirical literature supporting dimensional models of personality disorder that are closely aligned with the proposed model , in addition to the emerging body of work on the specific dimensions proposed for ICD‐11 . The ICD‐11 proposal has two elements.…”
mentioning
confidence: 99%
“…The differences in outcome shown between moderate and mild personality disorder in the ICD‐11 classification show the advantages of a single‐dimensional rating of personality disorder, and offset criticisms that such a simplified version of personality assessment is inadequate for clinicians prevented from using formal diagnostic categories (Pedersen et al, ). The evidence that there is good discrimination between the outcomes of those with mild and moderate personality disorder, without the need for further categories and qualified only by domain traits (Kim et al, ), shows an important advantage of the ICD‐11 dimensional system that is likely to be copied in future editions of DSM.…”
Section: Discussionmentioning
confidence: 99%